Perception Level of Social Ladder’s Concept and Significance among University Students - Alshashnieh, Mona Nimer (Journal of Humanities & Social Sciences, 2018)
This study aimed at identifying the perception level of social ladder’s concept and significance among university students. In order to achieve the study objectives, the researcher adopted both the descriptive-analytical. The researcher also developed a questionnaire to measure the perception level of social ladder’s concept and significance among university students. The questionnaire was applied on a stratified random sample consisting of (315) male and female students, of which (266) questionnaires were retrieved representing a response rate of (84.44%).The study results indicated that the perception level of social ladder’s concept and significance among university students was average. Furthermore, there were no differences in the perception level attributable to the following variables (academic specialization, marital status, and university level).The study recommended adopting all objectives of the suggested proposal along with its activities and programs. Additionally, for the purpose of reinforcing social ladder’s concept and elements, further studies on social ladder topic should be conducted and illustrative seminars and scientific conferences should be convened.
Keywords: university youth; social ladder